Predicting the revolving door phenomenon among patients with schizophrenic, affective disorders and non-organic psychoses - Gastal Fábio L; Andreoli Sérgio B; Quintana Maria Inês S; Gameiro Maurício Almeida; Leite Sérgio O; McGrath John (Universidade de São Paulo, 2000)
OBJECTIVE: The aim of the study was to identify the variables that predict the revolving door phenomenon in psychiatric hospital at the moment of a second admission. METHODS: The sample consisted of 3,093 patients who have been followed during 5 to 24 years after their first hospital admission due to schizophrenia, and affective or psychotic disorders. Those who had had four or more admissions during the study period were considered as revolving door patients. Logistic regression analyses were used to assess the impact of gender, age, marital status, urban conditions, diagnosis, mean period of stay on the first admission, interval between the first and second admissions on the patterns of hospitalization. RESULTS: The variables with the highest predictive power for readmission were the interval between first and second admissions, and the length of stay in the first admission. CONCLUSIONS: These data may help public health planners in providing optimal care to a small group of patients with more effective utilization of the available services.